2017
DOI: 10.7717/peerj.4153
|View full text |Cite
|
Sign up to set email alerts
|

Clinical significance of circulating immune cells in left- and right-sided colon cancer

Abstract: BackgroundLeft-sided and right-sided colon cancers (LCCs and RCCs, respectively) differ in their epidemiology, pathogenesis, genetic and epigenetic alterations, molecular pathways and prognosis. Notably, immune response gene expression profiles have been shown to differ between patients with LCC and patients with RCC. The immune system plays an important role in tumor immunosurveillance, and there is increasing evidence that peripheral blood immune cells have a profound influence on tumor prognosis. This study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 38 publications
2
8
0
Order By: Relevance
“…In the subgroup analyses, CIK cell immunotherapy was found to be significantly associated with an improved OS and PFS in patients with metastatic colon cancer, but this association was absent in patients with metastatic rectal cancer. This improvement, or lack thereof, might be explained by the fact that the prognosis and immune microenvironment are different between rectal cancer and colon cancer . Patients with rectal cancer have significantly better prognosis than those with colon cancer, especially for those with stage IV disease, which was also observed in our study.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…In the subgroup analyses, CIK cell immunotherapy was found to be significantly associated with an improved OS and PFS in patients with metastatic colon cancer, but this association was absent in patients with metastatic rectal cancer. This improvement, or lack thereof, might be explained by the fact that the prognosis and immune microenvironment are different between rectal cancer and colon cancer . Patients with rectal cancer have significantly better prognosis than those with colon cancer, especially for those with stage IV disease, which was also observed in our study.…”
Section: Discussionsupporting
confidence: 78%
“…This improvement, or lack thereof, might be explained by the fact that the prognosis and immune microenvironment are different between rectal cancer and colon cancer. [34][35][36] Patients with rectal cancer have significantly better prognosis than those with colon cancer, especially for those with stage IV disease, 34 which was also observed in our study. Thus, patients with metastatic rectal cancer might derive some benefit from CIK cell treatment, but this benefit would not be statistically significant.…”
Section: Effect Of Cik Cell Phenotypes On Patient Survivalsupporting
confidence: 86%
“…Su et al [25] reported the clinical signi cance of circulating immune cells at different colon tumour locations. In the present study, our results showed no correlation between ILC3 percentage and the different tumour regions ( Figure S1B and Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…Su et al [25] reported that different levels of circulating immune cells are associated with tumour location, stage, differentiation status, and lymphatic metastases in patients with colon cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Recurrence and metastasis are the main reasons for poor clinical treatment effects in colon cancer patients [ 4 ]. Studies show that the recurrence and metastasis of colon cancer is a complex multigene, multistage process involving a variety of factors [ 5 , 6 ]. Immune escape is one of the key reasons for the recurrence and metastasis of colon cancer [ 7 ].…”
Section: Introductionmentioning
confidence: 99%